2004
DOI: 10.1021/la048459k
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Serum Albumin Adsorption onto Colloidal Al2O3 Particles:  A New Model Based on Zeta Potential and UV−Vis Measurements

Abstract: We investigated the adsorption of bovine serum albumin (BSA) on colloidal Al2O3 particles in an aqueous environment. Changes in the zeta potential of the Al2O3 particles upon the adsorption of BSA were measured using an electro-acoustic technique. The mass of protein adsorbed was determined by using UV-vis spectroscopy. The change of the isoelectric point of the Al2O3 powder-protein suspension was found to be a function of adsorbed protein mass. It was shown that approximately one monolayer of BSA was needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
243
5
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(281 citation statements)
references
References 47 publications
(73 reference statements)
28
243
5
5
Order By: Relevance
“…Close to the pI, the electrostatic interaction is weak, and the protein will likely be randomly oriented at the NP surface, whereas at pH 7.5, protein orientation is dictated by charge density matching between oppositely charged domains. BSA does not undergo any significant conformational changes in the pH range from pH 4 to pH 8 [35], which reinforces the hypothesis of the initial interaction between PBCA NPs and BSA being predominantly electrostatic in nature [36].…”
Section: Np-stabilized Mbssupporting
confidence: 84%
“…Close to the pI, the electrostatic interaction is weak, and the protein will likely be randomly oriented at the NP surface, whereas at pH 7.5, protein orientation is dictated by charge density matching between oppositely charged domains. BSA does not undergo any significant conformational changes in the pH range from pH 4 to pH 8 [35], which reinforces the hypothesis of the initial interaction between PBCA NPs and BSA being predominantly electrostatic in nature [36].…”
Section: Np-stabilized Mbssupporting
confidence: 84%
“…Within the assumption of coinciding center of mass positions of the S distribution and of the whole protein, this indicates that the fully hydrated protein layer is as thick as d HSA ∼ 2Δz = 2z S ∼ 60-80 Å. For the width of the S distribution, we consistently obtain σ S = 20 ± 5 Å, corresponding to an FWHM = 48 ± 12 Å. Adsorption of serum albumin to Al oxide has been previously investigated using zeta-potential and UVVis measurements, and a layer thickness of about 55 Å under water was reported and interpreted as side-on configuration (31). Thicker serum albumin layers of more than 100 Å and up to 70 Å were reported for mica/water (36) and air/water interfaces (37), respectively.…”
Section: Resultssupporting
confidence: 55%
“…Furthermore, the accuracy of the UV-vis spectrometer of 2 milli absorbance limits the resolution of the recorded wavelength shifts. Compared with a protein with similar size like bovine serum albumin (BSA; 5.5 Â 5.5 Â 9 nm) 41 it is reported that 3.7 ( ± 0.2) Â 1,012 molecules bind per cm 2.42. This implies that B12 BSA molecules can bind to the surface of a 10-nm AuNP by an end-on mechanism.…”
Section: Resultsmentioning
confidence: 99%